Concretos refratários contendo agregados eutéticos eletrofundidos: energia de fratura e a resistência ao dano por choque térmico - Miyaji, Dan Yushin (2012)
The use of fused alumina-zirconia and mullite-zirconia eutectic aggregates can be an interesting choice to toughening high alumina castables, in order to produce good thermal shock damage resistant material. As a remarkable characteristic, the applying of such aggregates results in high fracture energy values, as a consequence of complex crack propagation process through the eutectic microstructure. However, the understanding of the relation between fracture energy and thermal shock damage requires special care, eventhough such relation is prospected by very know mathematical models. This is because the correct choice of sample dimentions showed to be very important to find relations between Hasselman s R -parameter and the experimental resistance to thermal shock The general results have indicated that the materials of the highest fracture energy values presented the highest thermal shock damage resistance. It was also verified that a high amount of aggregates in the castables did not produce reiforced microstructures, but more flexible materials, in a sense that the material s tolerance to crack opening had increased. This result is considered important because it shows that aggegates may play other roles besides the conventionaly known ones.